2016
DOI: 10.3389/fncir.2016.00036
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Imaging of Basal Forebrain Activity during Innate and Learned Behaviors

Abstract: The basal forebrain (BF) plays crucial roles in arousal, attention, and memory, and its impairment is associated with a variety of cognitive deficits. The BF consists of cholinergic, GABAergic, and glutamatergic neurons. Electrical or optogenetic stimulation of BF cholinergic neurons enhances cortical processing and behavioral performance, but the natural activity of these cells during behavior is only beginning to be characterized. Even less is known about GABAergic and glutamatergic neurons. Here, we perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
95
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 62 publications
9
95
2
Order By: Relevance
“…Furthermore, they discharge with bursts of action potentials during states associated with EEG theta activity. Behavioral studies revealed a rapid response to reinforcers [32,33]. Cholinergic signals in the cortex promote cortical activation [34], facilitate fast and dynamic plasticity of sensory perception [35], enhance the salience of stimuli [36] and promote long-lasting synaptic plasticity [37].…”
Section: How Do They Behave?mentioning
confidence: 99%
“…Furthermore, they discharge with bursts of action potentials during states associated with EEG theta activity. Behavioral studies revealed a rapid response to reinforcers [32,33]. Cholinergic signals in the cortex promote cortical activation [34], facilitate fast and dynamic plasticity of sensory perception [35], enhance the salience of stimuli [36] and promote long-lasting synaptic plasticity [37].…”
Section: How Do They Behave?mentioning
confidence: 99%
“…Towards this end we suggest two, not mutually-exclusive principles: 1) segregated inputs to the BFc convey specific cognitive operations and overlapping, common inputs mediate state-related changes; alternatively, 2) the complex set of inputs described in our study reflect multiple inbuilt templates for flexible control of cortical states in a modality-specific fashion via the tonic and phasic firing of cholinergic neurons (Hangya et al, 2015; Harrison et al, 2016). …”
Section: Discussionmentioning
confidence: 86%
“…However, recent studies suggest a more complex scenario that is characterized by a continuum of states rather than sharp transitions and, both in SWS and waking, finer distinctions can be made in terms of internal cortical dynamics and responsiveness to external stimuli (Harris and Thiele, 2011; McGinley et al, 2015; Vyazovskiy et al, 2011). The mechanism of how cortical arousal, movement-related activity (Harrison et al, 2016) and pupil micro-dilations (McGinley et al, 2015) are linked remains unexplained.…”
Section: Discussionmentioning
confidence: 99%
“…Prominent theories are based on evidence suggesting that pupil diameter tracks changes in the activity of noradrenergic LC neurons in humans and non-human primates (Aston-Jones and Cohen, 2005; Gilzenrat et al, 2010; Murphy et al, 2014a; Varazzani et al, 2015). Behavioral arousal is closely related to LC activity (Samuels and Szabadi, 2008a; Carter et al, 2010; Sara and Bouret, 2012) and pupil dilation in mice (Reimer et al, 2014; McGinley et al, 2015b; Vinck et al, 2015), as well as other neuromodulatory systems including acetylcholine (ACh; Eggermann et al, 2014; Lin et al, 2015; Harrison et al, 2016). Therefore, the task-related pupil dilations that we report are likely correlated with activation of pupil-linked neuromodulator systems, including LC neuron activity, but this remains to be tested by directly recording LC neurons in mice.…”
Section: Discussionmentioning
confidence: 99%